Vitamin D supplementation may improve symptoms in Meniere's disease. (July 2018) - Büki, Bela; Jünger, Heinz; Lundberg, Yunxia Wang
Abstract: In the last 4 years the authors observed a trend that correcting vitamin D deficiency in newly diagnosed cases of Meniere's disease decreased the necessity of the ablative therapy with intratympanic gentamicin. According to their hypothesis, vitamin D supplementation may indeed have a beneficial effect in Meniere's disease if the symptoms are caused by a local postviral autoimmune reaction. Vitamin D has a strong immunomodulatory role, one of which is the regulation of the expression of pro-inflammatory mediators. The authors suggest further epidemiological studies to decide if there is a connection between vitamin D deficiency and Meniere's disease.